The "Death Diamond": Rapid thrombelastography identifies lethal hyperfibrinolysis. Issue 6 (December 2015) - Chapman, Michael P.; Moore, Ernest E.; Moore, Hunter B.; Gonzalez, Eduardo; Morton, Alexander P.; Chandler, James; Fleming, Courtney D.; Ghasabyan, Arsen; Silliman, Christopher C.; Banerjee, Anirban; Sauaia, Angela
Abstract : BACKGROUND: Postinjury hyperfibrinolysis (HF), defined as LY30 of 3% or greater on rapid thrombelastography (rTEG), is associated with high mortality and large use of blood products. We observed that some cases of HF are reversible and are associated with patients who respond to hemostatic resuscitation; however, other cases of severe HF seem to be associated with these patients' inevitable demise. We therefore sought to define this unsurvivable subtype of HF as a recognizable rTEG tracing pattern. METHODS: We queried our trauma registry for patients who either died or spent at least 1 day in the intensive care unit, received at least 1 U of packed red blood cells, and had an admission rTEG. Within this group of 572 patients, we identified 42 pairs of nonsurvivors and survivors who matched on age, sex, injury mechanism, and New Injury Severity Score (NISS). We inspected the rTEG tracings to ascertain if any pattern was found exclusively within the nonsurviving group and applied these findings to the cohort of 572 patients to assess the predictive value for mortality. RESULTS: Within the matched group, 17% of the patients developed HF. Within the HF subgroup, a unique rTEG pattern was present in 14 HF patients who died and in none of the survivors. This pattern was a "diamond-shaped" tracing with a short time to maximum amplitude of 14 minutes or shorter and complete lysis before the LY30 point. When these criteria are applied to the 572 unmatched patients, this pattern had a 100% positive predictive value for mortality. CONCLUSION: Patients displaying the "death diamond" pattern on their admission rTEG are at higher risk for mortality. Given the volume of blood products and other resources that these patients consume, this thrombelastography pattern may represent an objective criterion to discontinue efforts at hemostatic resuscitation. LEVEL OF EVIDENCE: Prognostic/epidemiologic study, level III.